Paciente femenino de 50 años de edad con neumonía intrahospitalaria. - Rosero Gallegos, Fernando Javier (2021)
The following clinical case is about a patient with Intra-Hospital Pneumonia, a 60-year-old female patient, admitted to the hospital for a scheduled surgical intervention. After 3 days of intervention, the patient begins to present a cough of 2 days of productive evolution with purulent expectoration of a yellowish color of medium quantity plus fever of 38.6 ºC. The physical examination that was carried out indicates that the patient is asthenic, adynamic and vital signs are observed in which they have tachycardia, desaturation, data with which a chest X-ray is performed, which confirms the diagnosis of pneumonia. The following data collected in the previously described clinical case guides us to the presence of Intra-Hospital Pneumonia. It is one of the most frequent infections in the world, this type of disease is frequent in hospitalized patients, that is, after the first 72 hours if the patient presents symptoms equal to those of Intra-Hospital Pneumonia. It may be accompanied by other systemic symptoms more in relation to the generalized inflammatory immune response than due to the same pathology, however, it is important to establish during the questioning the characteristics of the cough and sputum (especially if hemoptysis), the presence of dyspnea, fever, presence of chest pain.